(untitled) (Physical Education, Health and Social Sciences, 2025)
Eugene Ionesco has often been accused of being “a peculiar anti-theatre man”. A drama represents “action on the stage” but Ionesco is less careful about the action and is more concerned with the language which fails to communicate even if it is used extensively to explain the complexity and absurdity of life. Since the proclamation of absurdist writers that “the world is devoid of meaning, purpose” and any divine authority, writers have become critical with the ability of language to communicate the meaning. The writers of 20th century communicate with silence, especially the playwrights have shown bare stages, short and trivial dialogues and long periods of silence on the stage. In the words of Wittgenstein, we can say, “language goes on holiday” (19). Each writer has used their own distinctive style to represent absurdity through “anti-plot, anti-hero, anti-dialogues and anti-characters” but Ionesco has used language with all its vigor and treasure to represent meaninglessness of our world. This paper will discuss Ionesco’s three major plays “The Bald Soprano”, “The Chair”, and “The Lesson” that how he has used language to convey the idea that no matter in what possible way a person tries to communicate, he always fails to connect to others, fails to convey meaning and fails to teach anything. The too much use of language by Ionesco also explores the gibberish quality of communication. The mumbling, babbling and the frequent sounds in the background also come to reinforce the uselessness of language usage in these plays. Language is ridiculed by language to give an insight into the abyss of our existence.